Screening for chloroquine maculopathy in populations with uncertain reliability in outcomes of automatic visual field testing - Paradee Kunavisarut (2018)
Purpose: The purpose of this study was to compare screening methods for the early detection of maculopathy in patients treated with chloroquine (CQ) or hydroxychloroquine (HCQ) and to identify the risk factors for the development of toxic maculopathy. Methods: We performed a prospective study of all 217 patients taking CQ and/or HCQ and seen in our center between July 2011 and December 2013. All subjects underwent a complete ocular examination, as well as spectral domain optical coherence tomography (SD-OCT), fundus autofluorescence (FAF), and 10-2 Humphrey visual field (10-2 HVF). Results: The median age of patients was 51 years, median CQ/HCQ duration was 40 months, and median cumulative dose was 180 g. The prevalence of at least two abnormal tests was 7.4% (16/217). SD-OCT had the highest sensitivity, specificity, predictive values and accuracy while 10-2 HVF showed in 30% of nonreliable results and had the lowest specificity and positive predictive value. In multivariate analysis, an age of older than 60 years (P = 0.002), CQ duration of more than 5 years (P < 0.001), and CQ dose more than 3 mg/kg/day (P = 0.005) were associated with toxicity. Conclusions: In patients with unreliable outcomes of 10-2 HVF testing, SD-OCT in combination with FAF might represent a suitable alternative screening tool for toxic maculopathy.